The future of Iranian social housing: a regional governance challenge - Ali Soltani; Goodarzi, Majid; Soltani, Zahra; Fahime Fadaei Jazi (Bulletin of Geography. Socio-economic Series, 2024)
Housing is a fundamental human necessity, shaping health, security and socio-economic well-being. The government of Iran has implemented various policies, plans and projects to ensure housing provision, but significant challenges remain, particularly in social housing. This study aims to identify and analyse the obstacles affecting the future development of social housing in Iran. Utilising a mixed-method approach, we conducted both quantitative and qualitative research, gathering expert insights through the Delphi method and analysing the data using cross-impact analysis via MICMAC software. The results revealed four critical challenges: limited loan repayment ability, currency instability, social issues within low-income communities, and policy isolation. These findings underscore the need for policymakers to adopt a comprehensive strategy that addresses financial, social and political fragmentation to ensure sustainable and equitable access to social housing for low-income residents.